2016
DOI: 10.1371/journal.pone.0148045
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cortico-Striatal Connectivity in Offspring of Schizophrenia Patients Relative to Offspring of Bipolar Patients and Controls

Abstract: Schizophrenia (SZ) and bipolar disorder (BD) share clinical features, genetic risk factors and neuroimaging abnormalities. There is evidence of disrupted connectivity in resting state networks in patients with SZ and BD and their unaffected relatives. Resting state networks are known to undergo reorganization during youth coinciding with the period of increased incidence for both disorders. We therefore focused on characterizing resting state network connectivity in youth at familial risk for SZ or BD to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 61 publications
(73 reference statements)
2
12
0
Order By: Relevance
“…We found no significant differences in unaffected individuals at familial risk of mood disorder compared to controls. This is in contrast to a number of potential trait markers that have so far been identified for BD, eg widespread white matter reductions, thinning of temporal brain regions, and functional activation increases in the amygdala during task performance, but consistent with other recent studies that found no differences in functional resting‐state connectivity in individuals at familial risk for mood disorder, suggesting that these differences in connectivity may not be the most sensitive biomarkers of familial risk.…”
Section: Discussionsupporting
confidence: 87%
“…We found no significant differences in unaffected individuals at familial risk of mood disorder compared to controls. This is in contrast to a number of potential trait markers that have so far been identified for BD, eg widespread white matter reductions, thinning of temporal brain regions, and functional activation increases in the amygdala during task performance, but consistent with other recent studies that found no differences in functional resting‐state connectivity in individuals at familial risk for mood disorder, suggesting that these differences in connectivity may not be the most sensitive biomarkers of familial risk.…”
Section: Discussionsupporting
confidence: 87%
“…According to the tripartite model of frontostriatal circuits which are defined by their cortical inputs, the sensorimotor loop connects the somatosensory and motor‐related cortices with the dorsal caudal putamen and dorsal rostral putamen, associative loop connects the dlPFC with the dorsal caudate and ventral rostral putamen, and the limbic loop connects the ACC, OFC, and ventromedial PFC with the VS (including the nucleus accumbens and ventral parts of the caudate and putamen). Among the above loops, limbic and associative loop dysfunction have been reported frequently in patients with SZ or individuals at a high risk for SZ (Juckel et al, ; Lancaster et al, ; Rausch et al, ; Sarpal et al, ; Sole‐Padulles et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Within the DMN, regions display only limited connectivity in childhood and become strongly functional connected by adulthood (Fair et al, 2008). In particular, anterior DMN connectivity of the rACC was shown to increase significantly between age 7 and 18 (Sole-Padulles et al, 2016). Similarly, looking at connectivity of the SN across development, significantly stronger functional connectivity between the dACC and anterior insula has been observed among adults relative to children (Uddin et al, 2011), with dACC connectivity increasing significantly between age 7–18 (Sole-Padulles et al, 2016).…”
Section: Typical Development Of Functional Acc Connectivity: Reviewmentioning
confidence: 99%
“…In particular, anterior DMN connectivity of the rACC was shown to increase significantly between age 7 and 18 (Sole-Padulles et al, 2016). Similarly, looking at connectivity of the SN across development, significantly stronger functional connectivity between the dACC and anterior insula has been observed among adults relative to children (Uddin et al, 2011), with dACC connectivity increasing significantly between age 7–18 (Sole-Padulles et al, 2016). Furthermore, a direct comparison of structural and functional connectivity of the DMN across development identified the cingulum to be the most immature link in this network in childhood, and demonstrated that cingulum FA was positively correlated with DMN functional connectivity in adulthood (Supekar et al, 2010).…”
Section: Typical Development Of Functional Acc Connectivity: Reviewmentioning
confidence: 99%